Edukasi Pupuk Organik dan Non Organik Serta Pengukuran pH Tanah Di Desa Tlagah - Suratin Lukmana; Imroatul Islamia; Takwallo (CV. BAROKAH PUBLISHER, 2026)
Agriculture is one of the livelihoods of the community. In caring for their crops, farmers usually use chemical fertilizers; however, they sometimes pay little attention to seed quality and soil type when applying them. In addition to chemical fertilizers, farmers also use organic fertilizers. Organic fertilizer raw materials are abundantly available in the household environment, inexpensive, and easily accessible. Various organic wastes from households, agriculture, and livestock activities, such as vegetable residues, fruit peels, and food waste, can be processed into high-quality organic fertilizer. Although farmers are able to produce organic fertilizer independently using natural materials, assistance from experts is still required to ensure consistent quality. Providing knowledge regarding plant nutrient elements derived from organic materials is expected to enhance the community’s capacity to produce organic fertilizer. The Community Service Team of STAI Darussalam initiated a program to introduce the management of kitchen waste into organic fertilizer with the aim of improving the knowledge and skills of partner communities, farmers, and farming households in Tlagah Village regarding the functions, benefits, production methods, and application of organic fertilizer on agricultural land. The methods employed included lectures, discussions, and soil condition assessments. The results indicate that the community was able to process and utilize organic waste in an environmentally friendly manner. This activity was positively received as it not only provided direct benefits but also strengthened partnerships among community members and between the community and higher education institutions in supporting sustainable development.